2014
DOI: 10.1074/jbc.m113.508416
|View full text |Cite
|
Sign up to set email alerts
|

The Cyp2c44 Epoxygenase Regulates Epithelial Sodium Channel Activity and the Blood Pressure Responses to Increased Dietary Salt

Abstract: Background: Epoxyeicosatrienoic acids (EETs) regulate sodium excretion in the distal nephron. Results: Lack of a Cyp2c44 epoxygenase blunts the ERK1/2-mediated inhibition of ENaC and causes salt-sensitive hypertension. Conclusion: Cyp2c44 is the epoxygenase responsible for the synthesis of natriuretic EETs during increased salt intake. Significance: Roles for the human CYP2C8 and CYP2C9 epoxygenases as antihypertensive therapeutic targets are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
108
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(110 citation statements)
references
References 50 publications
1
108
0
Order By: Relevance
“…Salt stimulates renal microsomal biosynthesis of EETs in normal Sprague Dawley 4 and Dahl-R rats, 5 whereas this response is absent in the salt-sensitive (SS) Dahl-S strain, leading to hypertension with reduced renal expression of the epoxygenase CYP2C23 and urine excretion of EETs. 5 In SR rats, the epoxygenase inhibitor clotrimazole decreases urinary EETs and reproduces SS hypertension.5 Cyp4a10 knockout mice, which have reduced renal epoxygenase (Cyp2c44) activity, 6 and the Cyp2c44 knockout, 7 have diminished urine EETs and amiloride-sensitive hypertension. This is associated with decreased inactivating threonine phosphorylation of γENaC (epithelial sodium channel), 7 which is reversible by the PPARα ligands that stimulate epoxygenases.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Salt stimulates renal microsomal biosynthesis of EETs in normal Sprague Dawley 4 and Dahl-R rats, 5 whereas this response is absent in the salt-sensitive (SS) Dahl-S strain, leading to hypertension with reduced renal expression of the epoxygenase CYP2C23 and urine excretion of EETs. 5 In SR rats, the epoxygenase inhibitor clotrimazole decreases urinary EETs and reproduces SS hypertension.5 Cyp4a10 knockout mice, which have reduced renal epoxygenase (Cyp2c44) activity, 6 and the Cyp2c44 knockout, 7 have diminished urine EETs and amiloride-sensitive hypertension. This is associated with decreased inactivating threonine phosphorylation of γENaC (epithelial sodium channel), 7 which is reversible by the PPARα ligands that stimulate epoxygenases.…”
mentioning
confidence: 99%
“…5 Cyp4a10 knockout mice, which have reduced renal epoxygenase (Cyp2c44) activity, 6 and the Cyp2c44 knockout, 7 have diminished urine EETs and amiloride-sensitive hypertension. This is associated with decreased inactivating threonine phosphorylation of γENaC (epithelial sodium channel), 7 which is reversible by the PPARα ligands that stimulate epoxygenases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CYP2C44 normally generates EETs to suppress ENaC activity and limit sensitivity to high-salt diet (Capdevila et al, 2014). Our data suggest that Cyp2c44 is the predominant Cyp2c expressed in the kidney.…”
mentioning
confidence: 58%
“…Cyp2c29, Cyp2c37, Cyp2c38, Cyp2c39, Cyp2c40, Cyp2c50, and Cyp2c54 are all predominantly expressed in liver (Luo et al, 1998;Wang et al, 2004). Cyp2c55 is highly expressed in colon (Wang et al, 2004), whereas the Cyp2c44 epoxygenase has been shown to be expressed in liver and the renal collecting duct (DeLozier et al, 2004;Capdevila et al, 2014). The remaining mouse Cyp2c cDNAs (Cyp2c65, Cyp2c66, Cyp2c67, Cyp2c68, Cyp2c69, and Cyp2c70) were not previously cloned, and no analysis of their tissue distribution at the RNA level has been reported.…”
Section: Introductionmentioning
confidence: 99%